Multicellularity: How contraction has shaped evolution - Thattai, Mukund (eLife, 2019)
Two unicellular relatives of animals reveal that coordinated contractions of groups of cells using actomyosin predated animal multicellularity during evolution.
Keywords: cellularization; coenocyte; evolution; epithelium; actin; multicellularity